Digital Ethno-Religious Determinants of Santri Religious Behavior: Technology Attitudes as a Mediator and Pesantren Culture as a Moderator - Khafidin, Zaenal; Ihsan, Ihsan; Masrukhin, Masrukhin; Nurfaizal, Yusmedi; Barros, Agapito (EDUKASIA, 2025)
This study aims to examine how Islamic digital literacy and digital religious identity influence santri religious behavior. The research addresses the issue of increasing digital exposure among pesantren students and how this exposure shapes their religious expression. The study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (SmartPLS4) and involves 100 Madrasah Aliyah students from both salaf and modern pesantren in Kudus, Indonesia. The results show that Islamic digital literacy and digital religious identity significantly predict religious behavior, both directly and indirectly through attitudes toward technology. The findings that pesantren culture strengthens the effect of attitudes on religious behavior. This study contributes a mediation moderation model that explains how digital competence, identity, and cultural context interact to shape religious behavior among santri, offering insights for culturally grounded digital literacy development in Islamic education.